Poluição atmosférica gerada pela indústria sucroalcooleira e seus impactos na saúde da Paraíba e Rio Grande do Norte - Camargo, Lúcia Magnólia Albuquerque Soares de (2013)
The idea that the environment and health have an intimate relationship with each other is now recognized worldwide. However, as this idea appeared and solidified, the sugar and alcohol industries also appeared and solidified, showing two types of development: economic, and diseases resulting from the industrialization process of sugarcane. This study had as objective to evaluate the health effects caused by exposure to pollutants generated by the activities of the sugar and alcohol industries from the states of Paraíba and Rio Grande do Norte, between 2001 and 2011. It was analyzed the occurrence of temporal pattern of endocrine, cardiovascular, respiratory and digestive over the period proposed in the following towns: Itabaiana, Pedras de Fogo and Pilar from Paraíba State, and also in Arês, Monte Alegre and São José do Mipibú, State of Rio Grande do Norte, in the indicated period. Were included in this study, the type of ecological time series and descriptive for those towns which are located in the dispersion plume of pollutants created by the characteristics activities of the sugarcane industry, in particular the burning of sugar cane, held before harvest. The lack of an air quality monitoring system in the analyzed regions, did not allow the measurement of exposure to air pollutants, quantitatively. The data were treated under the form of annual fees for periods of crop harvests and for total admissions of the four disease groups analyzed; and for the seasonal pattern of the four disease groups, were built graphics with totals of admissions for each of the disease groups in the cities of Paraiba and Rio Grande do Norte. In general, it was observed that there is prevalence in the harvest periods of the admission rates of disease groups analyzed in this study. It was suggested that hospitalizations for these disease groups were influenced by environmental conditions occasioned by sugar and alcohol industries in populations of host towns in the surroundings, together with the lack of specific legislation to control the burning of sugarcane in the locations of interest, and the lack of a public regulatory agency for these pollutants in this region.